PENGARUH PENYAJIAN DAN AKSESIBILITAS LAPORAN KEUANGAN DAERAH TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH - Fauziyah, Miftahul Reza; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine the influence of the presentation local financial statement and the accessibility of local financial statements to the accountability of financial management. This research is a quantitative research. The population is the Local Apparaturs Working Units (SKPD) in the environment of the Municipal of Surabaya City. The sampling technique hasd been carried out by using purposive sampling method. The data collection techniques has been conducted in this research by using survey method. The data has been carried out by using the primary data in the form of questionnaires which have been issued to respondents. The analytical method has been run by using multiple linear regression analysis and the SPSS (Statistical Product and Services Solutions) 20.0.th version. The results of this research shows that the presentation of local financial statement has positive influence to the local financial management accountability and the accessibility of financial statements has positive influenceto the local financial management accountability.Keywords: The presentation of local financial statements, the accessibility of local financial statements, the accountability of local financial management.